2003
DOI: 10.1194/jlr.m200450-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Covalent binding of hydroxy-alkenals 4-HDDE, 4-HHE, and 4-HNE to ethanolamine phospholipid subclasses

Abstract: Lipid oxidation is implicated in a wide range of pathophysiogical disorders, and leads to reactive compounds such as fatty aldehydes, of which the most well known is 4-hydroxy-2 E-nonenal (4-HNE) issued from 15-hydroperoxyeicosatetraenoic acid (15-HpETE), an arachidonic acid (AA) product. In addition to 15-HpETE, 12(S)-HpETE is synthesized by 12-lipoxygenation of platelet AA. We first show that 12-HpETE can be degraded in vitro into 4-hydroxydodeca-(2 E ,6 Z )-dienal (4-HDDE), a specific aldehyde homologous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 53 publications
1
94
0
1
Order By: Relevance
“…The contribution made by beta cellgenerated 4-hydroxyalkenals to this process is unclear. High levels of 4-hydroxyalkenals and their metabolites have been linked to the development of diabetic complications [25,35,38,[46][47][48]. Indeed, exposure of beta cell cultures and rat isolated islets to high levels of 4-HNE induced apoptosis and cell death [13,27].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution made by beta cellgenerated 4-hydroxyalkenals to this process is unclear. High levels of 4-hydroxyalkenals and their metabolites have been linked to the development of diabetic complications [25,35,38,[46][47][48]. Indeed, exposure of beta cell cultures and rat isolated islets to high levels of 4-HNE induced apoptosis and cell death [13,27].…”
Section: Discussionmentioning
confidence: 99%
“…HDDE is formed from 12-HpETE, which is thought to be generated enzymatically by 12-lipoxygenase [43]. HNE can also be produced enzymatically by two different 15-lipoxygenases (15-LOX) acting on arachidonate [25].…”
Section: Alkanalsmentioning
confidence: 99%
“…It has a longer aliphatic chain and is more hydrophobic than HNE and HHE, which has previously been suggested to lead to higher reactivity toward less polar biomolecules such as phospholipids. Studies carried out to compare the reactivity of HDDE, HNE and HHE with phosphatidylethanolamine showed that HDDE was the most reactive with the headgroup, resulting in more adduct formation with several different PE molecular species, followed by HNE and the least reactive being HHE [43]. It is also important to note that oxidation of the fatty acyl chains often occurs in phospholipid-esterified forms, and the Hock and β cleavages lead to analogous esterified aldehydes as well as the free forms discussed above.…”
Section: Alkanalsmentioning
confidence: 99%
“…(Figure 1b) of the reaction products of acrolein with 18:1a/18:1-GPEtn. Previously, it was determined that one of the major products formed upon the reaction of primary amino groups on peptides with acrolein resulted from the 1,4-Michael addition of two acrolein molecules and subsequent aldol condensation followed by dehydration (14). An analogous aldol condensation product (IV) from our 18:1a/18:1-GPEtn standard would be expected to have a [M + H] + at m/z 856.5.…”
Section: Resultsmentioning
confidence: 99%